Association between Inpatient Delirium and Hospital Readmission in Patients ≥ 65 Years of Age: A Retrospective Cohort Study. Issue 4 (1st April 2019) - LaHue, Sara C; Douglas, Vanja C.; Kuo, Teresa; Conell, Carol A; Liu, Vincent X; Josephson, S Andrew; Angel, Clay; Brooks, Kristen B
Abstract : BACKGROUND: Delirium affects more than seven million hospitalized adults in the United States annually. However, its impact on postdischarge healthcare utilization remains unclear. OBJECTIVE: To determine the association between delirium and 30‐day hospital readmission. DESIGN: A retrospective cohort study. SETTING: A general community medical and surgical hospital. PATIENTS: All adults who were at least 65 years old, without a history of delirium or alcohol‐related delirium, and were hospitalized from September 2010 to March 2015. MEASUREMENTS: The patients deemed at risk for or displaying symptoms of delirium were screened by nurses using the Confusion Assessment Method with a follow‐up by a staff psychiatrist for a subset of screen‐positive patients. Patients with delirium confirmed by a staff psychiatrist were compared with those without delirium. The primary outcome was the 30‐day readmission rate. The secondary outcomes included emergency department (ED) visits 30 days postdischarge, mortality during hospitalization and 30 days postdischarge, and discharge location. RESULTS: The cohort included 718 delirious patients and 7, 927 nondelirious patients. Using an unweighted multivariable logistic regression, delirium was determined to be significantly associated with the increased odds of readmission within 30 days of discharge (odds ratio (OR): 2.60; 95% CI, 1.96‐3.44; P < .0001). Delirium was also significantly ( P < .0001) associated with ED visits within 30 days postdischarge (OR: 2.18; 95% CI: 1.77‐2.69) and discharge to a facility (OR: 2.52; 95% CI: 2.09‐3.01). CONCLUSIONS: Delirium is a significant predictor of hospital readmission, ED visits, and discharge to a location other than home. Delirious patients should be targeted to reduce postdischarge healthcare utilization.